Inovasi Digital dalam Pemesanan Makanan: Aplikasi Mobile Android untuk Pemesanan Ayam Geprek Secara Online - Nugraha, Rivaldi Kenny; Pramudwiatmoko, Arif (Universitas Hamzanwadi, 2024)
The development of information technology has increased the popularity of online food ordering, but many small restaurants still use conventional methods, so Android Mobile-based ordering systems are an effective solution to increase efficiency and reduce errors. This research aims to produce a food ordering application, namely geprek chicken at Warung Keysha online based on Mobile Android. This application builds the system using a Research and Development (R&D) strategy in conjunction with the Rapid Application Development (RAD) model, which comprises three stages: needs planning, RAD design workshop, and implementation. Research and Development (R&D) approach to build the system. The program was tested using black box testing, which makes sure that every system function works as intended.. Fifty customers were the subject of the study to measure user reactions. questionnaires for data collection, and quantitative descriptive methods for data analysis. The findings showed that the developed application received a feasibility test result of 94% (very feasible).